The Effect of Pesticide Exposure on Women Farmers of Reproductive Age on Growth and Development Disorders of Children Born: A Systematic Literature Review - Friska Eka Fitria; Nur Afrainin Syah; Jamsari Jamsari; Yuniar Lestari (Postgraduate, University of Mataram, 2023)
The large number of children suffering from ADHD and autism today is a result of the increasing use of pesticides in agriculture. This applies to women farmers of childbearing age who work in agricultural settings or women whose work is related to the use of pesticides. Pesticides are a mixture of several chemicals used to control pests and protect plants. With the use of pesticides, yields obtained increased significantly. This study aims to examine the effect of exposure to pesticides on female farmers of childbearing age on growth and development disorders of children born. The review was conducted according to state-of-the-art methods using selected reporting item guidelines for reviews and meta-analyses (PRISMA). We reviewed the literature from several publications and analyzed the effect of exposure to pesticides on female farmers of childbearing age on developmental disorders of the children they were born with. The results of this study are the effect of exposure to pesticides on female farmers of childbearing age on birth defects. The use of pesticides causes pesticide poisoning. Accumulation of pesticides at a certain threshold has a negative impact on the body, namely brain disorders, tumors, cancer, even in pregnant women can cause birth defects. Apart from adults, pesticides also have a negative impact on children